A comprehensive analysis of the optical and thermal performance of solar absorber coatings under concentrated flux conditions. (June 2022) - Martínez-Manuel, Leopoldo; González-Canché, Nancy G.; López-Sosa, Luis B.; Carrillo, Jose G.; Wang, Wujun; Pineda-Arellano, Carlos A.; Cervantes, Fernando; Gil, Juan Jose Alvarado; Peña-Cruz, Manuel I.
Highlights: A high flux solar simulator is the radiative flux source for experimentation. The calorimeter provides the versatility to insert coated test plates. Four commercial coatings and one forest biomass soot coating were evaluated. Optical and thermal properties of exposed coatings have been reported. Abstract: Solar Absorber Coatings (SACs) are widely used materials for improving thermal efficiencies of solar receivers. Traditionally, these SACs are investigated using heat treatments to test their optical-thermal properties; however, tests under concentrated flux conditions are still required. In this work, the thermal efficiency of different SACs is experimentally evaluated and compared. The analyzed SACs are: (1) Pyromark®2500, (2) Solkote®, (3) Thurmalox®250, (4) Comex® and (5) a new Soot from Forest Biomass (SFB) based coating. To assess the SACs performance, a High Flux Solar Simulator along with a calorimetric test bench are implemented under a well-controlled indoor environment applying two levels of concentrated irradiance of 100 ± 3 kW/ m 2 and 415 ± 12 kW/ m 2 named low and high flux level, respectively. Results show that, for a low flux level, the analyzed coatings present thermal efficiencies in a range from 91.74% to 83.24%, exhibiting a slightly close performance in most of the cases. Correspondingly, for a high flux level, the efficiencies range from 88.69% to 72.69%, with Pyromark®2500 being the most efficient in both cases. In addition, variations in the optical properties are reported for the experimental campaign with the high flux level, observing slight changes in the spectral absorptance and emittance. From these results, Pyromark presents the highest drop in solar absorptance of 1.22%, which is attributed to microcracks observed through the Scanning Electron Microscope (SEM). Thus, the presented approach can provide valuable information about the effects that concentrated flux levels can have in the optical-thermal performance of the analyzed samples.